HOMEMADE HELICOPTER DESIGN AND VIBRATIONAL ANALYSIS - John Ngangsi Ngah,; Julius K. Tangka,; Mathias N.W. EVINA, (International Journal of Innovations in Engineering Research and Technology, 2022)
In this work, the homemade helicopter aerodynamics is analyzed. The helicopter model is the Sikorsky configuration, in which the   main     rotor   is in perpendicular combination to the tail rotor.  The rotors are articulated and their blades are rigid. The main rotor implementation takes into account flap and feather degrees of freedom  for  each  of  the equispaced    blades    as    well    as    their    dynamic couplings.Transmitted vibrations due to the rotating rotors blades on the body structure (fuselage) are   studied.   This   work   presents   an aerodynamic model that allows us to analyse vibrational transmissions on the fuselage (body) of the homemade helicopter. Vibrations in helicopters is a common problem which involves complex interactions between the inertials, structural loads and aerodynamic loads especially in homemade helicopters.  The major source of vibrations in helicopters is the main rotor. These vibrations affect the functionality, durability of the engine component parts, increases maintenance frequency (cost) and structural failures. The aerodynamic model has been built up implementing blade element theory.  The aerodynamic load creates vibrations on the homemade helicopter and these are analyzed on the fuselage by using short time Fourier transform that brings out the vibrational spectrum.   The   results of the analyzed serves as a guide to improve the functionality, durability, maintenance frequency and to reduce structural failures of the rotor craft. The results are used as reference characteristics in the construction of rubber engine mount for engine seatings as well as the crew seats, control panel and camera suspensions.